Intelligent Control of Photovoltaic Grid-connected Using Fuzzy Logic Based Incremental Conductance. (2015) - Louzazni, Mohamed; Aroudam, Elhassan
Abstract: This paper presents an intelligent control of the output power energy from the three-phase grid connected photovoltaic (PV) array, based on fuzzy logic controller and incremental conductance to optimize and track the maximum power point tracking (MPPT) from the PV under varying temperature and irradiance conditions. The control shown better performances and effectiveness compared to Perturb & Observe (P&O). The fuzzy logic control, enhanced by the algorithm can respond quickly to changes in the external environment and make sure the PV is always working at the MPPT and improve the efficiency and the stability of three-phase photovoltaic grid-connected. The intelligent controller improves the incremental conductance search method by fuzzifying, the rules of such techniques and will find exactly the MPPT. Finally, the results verify the correctness and availability of the PV system under various weather conditions.